Controlled Creation of Contact Cracks in Additive Manufactured Components - Daniel Preston; Ahmed Ashour; Julian Wright; James Watts; Daniel Sanmartin; Jacques Wood (Applied Sciences, 2023)
Techniques for the controlled seeding and growth of cracks are urgently required for non-destructive testing technique evaluation, particularly for additive manufactured (AM) samples. This paper describes a method that uses a combination of the tensile load and the resonance excitation of notched AM samples, with in situ monitoring of the resonance frequency serving to track the crack dimensions. Mechanical low-cycle fatigue cracks, ranging in length from ~0.3 mm to ~5 mm, were successfully created in five AM samples using this technique. The samples were non-destructively characterized using optical microscopy and Nonlinear Resonance (NLR) testing. The exploitation of resonance enabled the concentration of a significant number of stress cycles on the samples in much shorter timespans than conventional fatigue testing, enabling a high throughput while utilizing compact components. Furthermore, the tracking of the resonance frequency shift throughout the process enabled non-invasive and no-contact real-time condition monitoring.